Psychic versus Economic Barriers to Vaccine Take-Up : Evidence from a Field Experiment in Nigeria - Sato, Ryoko; Takasaki, Yoshito (Published by Oxford University Press on behalf of the World Bank, 2021)
This paper experimentally evaluates the relative importance of psychic costs of tetanus vaccination compared to monetary costs among women in rural Nigeria. We compare vaccine take-up between two conditions to receive cash incentives: clinic attendance vs. vaccine take-up. Because the only difference between these two conditions is whether a woman was required to receive a vaccine upon arrival at the clinic, the difference in clinic attendance between these two groups captures the psychic costs of vaccination. Contrary to conventional wisdom, we find no evidence for significant psychic costs. Priming about disease severity increases the perceived severity of disease, but not vaccine take-up. Monetary costs strongly affect vaccination decisions.